Creating access to powerful knowledge in accounting education: a case study of pedagogies used in an accountancy diploma - West, Janét (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning)
Students enter universities to obtain a qualification that they believe will enhance their chances of employment and thereby a better future. But the World Economic Forum states that the world of work is changing so fast that 75% of companies are not prepared for the pace at which their industries are changing. The field of accounting, and accounting education in particular, is facing significant challenges as accountants change from being 'number crunchers' to engaging business partners. There is also a decrease in the demand for accountants, at the same time as increasing complaints that accounting graduates are unprepared for their work. These contextual challenges raise the question of 'What can higher education institutions do to prepare students for a future of rapid change and uncertainty, specifically within the field of accounting?' This study argues that epistemological access to powerful knowledge is essential for creating lifelong learners that can adapt to change. The study draws on Legitimation Code Theory (LCT) to visualise the powerful knowledge that students require access to in two thirdyear modules within a Diploma of Accounting. This is followed by an analysis of the pedagogies used in the two modules and how access to powerful knowledge is enabled (or hindered) through the pedagogical practices. Data include lecturer observations, course documents and interviews. The study found that there are significant differences between the knowledge structures of the modules, despite them being part of the same discipline. Furthermore, through the analysis I was able to identify key patterns in the pedagogies that enable access to powerful knowledge as well as pedagogical approaches that may constrain access to powerful knowledge. The findings of this study can help accounting lecturers as well as lecturers in similar disciplines to consider how their pedagogical practices enable epistemological access to the target powerful knowledge of their discipline.
Keywords: Accounting-- Study and teaching -- South Africa; Educational change; Knowledge, Theory of; Critical thinking; Semantics